Bilateral Opportunism in Buyer–supplier Partnerships. Issue 3 (2nd July 2020) - Wölfel, Joachim; Grosse-Ruyken, Pan Theo
ABSTRACT: Purpose: Literature analyzes interorganizational relationships mostly from a relational perspective by emphasizing partnerships' positive aspects. Yet business reality is often less romantic and more opportunistic. Especially within the automotive industry opportunistic behaviors often cause extreme reactions in both partners, resulting in poisoned relationships. This study examines the effects of bilateral opportunism between buyers and suppliers on both partners' relationship induced financial performance, using an automotive industrial setting of new product development (NPD) partnerships. Furthermore, we evaluate the "opportunistic fit" between both partners to assess whether partnerships are characterized by opportunistic parity or unilateral domination. Methodology: The empirical analyses are based on primary data from 147 NPD partnerships between tier-1 suppliers and automotive manufacturers (OEMs), exclusively drawn from the suppliers' perspective. Data were statistically analyzed using structural equation modeling (SEM) with SPSS AMOS. Findings: Our findings suggest that large parts of NPD partnerships between suppliers and OEMs are opportunistically lopsided, meaning that they are unilaterally dominated. With reciprocity, firms are able to counterbalance the influence of partnership opportunism and its effects on financial performance by themselves. Financial benefits achieved by opportunistically striving after economic self-interest are eliminated, in case the deprived partner attempts to opportunistically adjust its inequitable position. Our results show that opportunistic firms can benefit from immediate improvements in individual financial performance, but only until the disadvantaged partner has a counter opportunistic reaction. When the opportunism of both partners is at parity, firms cannot generate any individual increases in financial performance by acting opportunistically, highlighting the significance of bilateral opportunism for B2B business scholars. Originality: This paper enhances the understanding of business relationships in industries with strong power imbalance between the buyer and the supplier firm. The authors introduce the idea of "bilateral opportunism" and "opportunistic parity" to the B2B marketing literature. These concepts shed light on the reality of business relationships, in particular in industries with high power imbalance, such as the automotive industry. Descriptive information highlights the relevance of the opportunistic parity concept.